Odonata (Insecta) richness in Atlantic Forests from Minas Gerais state, Brazil - Anjos, Caio Silva dos; Pereira de Gouvêa, Taiguara; Vilela, Diogo Silva; Souza, Marcos Magalhães de (EntomoBrasilis, 2023)
Inventories provide important information about species, both from a biogeographic perspective and in terms of their conservation status. Among insects, dragonflies are extensively surveyed in Brazil; however, significant knowledge gaps still exist regarding the distribution of these organisms in the country, particularly in threatened biomes such as the Atlantic Forest. In this study, we present data on an Odonata community collected in the Serra do Papagaio State Park between 2015 and 2016. We recorded 64 species, including six new records for the state of Minas Gerais, along with ten species with problematic conservation status, either due to a lack of distribution data or some degree of extinction risk. Our results highlight the importance of inventories in expanding our knowledge of species distribution and providing data that can aid in the assessment of their conservation status.